Design, preparation, and performance of a novel organic–inorganic composite coating with high adhesion and protection for concrete. (1st April 2022) - Luo, Shunjie; Wei, Jiangxiong; Xu, Weiting; Chen, Yang; Huang, Haoliang; Hu, Jie; Yu, Qijun
Abstract: To guarantee concrete serving in harsh and corrosive environments, a novel functional organic–inorganic composite coating with high adhesion and barrier performance was designed in this work. The prepared composite coating was assembled by incorporating kaolinite nanosheets into permeable epoxy resin via ultrasonic mixing techniques. The dispersed nanosheets endowed the epoxy with reinforced cross-linking, high temperature stability and enhanced barrier property. The composite coatings exhibited stable bonding with the concrete matrix and excellent corrosion resistance. The composite coating with 1 wt% nanosheets showed an optimum comprehensive performance. It could infiltrate concrete with a depth of 2376 μm and the dehydration reaction temperature of the coating was 168.1 °C. The total charge passed and maximum oxygen transmission was reduced to 63C and 4.438 cc/m 2 day, respectively. The pull-off strength of the composite coating with concrete was 5.68 MPa, which was 32% higher than the permeable epoxy. The designed composite coatings provided strong bonding and high barrier to the concrete structure, showing potential application in the anti-corrosion engineering and construction field. Graphical abstract: Image 1